Pelatihan Office Visio Untuk Pembelajaran di Sekolah Menengah Kejuruan Penerbangan Dhirgantara Curug – Tangerang - Yayuk Suprihartini; Taryana Taryana; Elvi Amir; Rini Sadiatmi; Rubby Soebiantoro (Jurnal Abdimas ADPI Sains dan Teknologi, 2023)
Computer technology is very helpful for human tasks and has become an important need in everyday life. Computer technology has developed so rapidly that each student have to master it to make reporting easier.one of the programs software from windows is Microsoft office visio to create various diagrams such as flowcharts, block diagrams and data flow diagrams quickly for various reports. various diagrams such as flowcharts, block diagrams and data flow diagrams quickly for various reports.. So it is necessary to equip these students with the Visio program. This is the background to the need for Community Service with the title "Visio Training at the Dirghantara Aviation Vocational High School." The purpose of this Community Service activity is for students to be able to draw techniques using computers to support their activities. The method used in this activity was to provide theoretical material about office visio and continued with office visio training to grade 10 students at the Dirghantara Aviation Vocational High School. The discussion of the training included students being given office visio materials related to usability, tools in the program and image editing. Then students are given a problem making technical drawings about electrical networks to practice the Visio program. The conclusion of this activity is that all students can understand and use the Visio program well. As well as the Visio program is very useful to support their activities, especially when later making reports on field work practices.